Impact of utilising a multimedia based tense tool on students’ motivation, cognitive load and language learning experience - Nadia, Refat (2022)
Widespread utilization of evolving technologies offers immense possibilities in enhancing learning. Multimedia-based technology emerges from this trend and draws concern of researchers who are devotedly developing instructions for divergent areas of learning. Language learning is one of the most demanding areas where the practice of different kinds of technologies are adopted. More specifically, English language learning is performed using the multimedia technology. While much research has been done on the implication of multimedia-based English language learning and educational practices fostering learning approaches, relatively little concern has been given on instructional design based on theoretical foundations. Most importantly, to initiate meaningful learning, designing proper instructions relating to motivation enhancement and cognitive load management, there is a lack of studies, particularly in the context of developing countries like Malaysia. Furthermore, in Malaysia, English tenses as one of the vital items of grammar require more attention from the instructional designers in order to achieve the utmost effective learning. This study sought to fill this gap by developing such a Multimedia-Based Tense Tool (MBTT) where the instructions are focused on integrating the motivational model and cognitive aspects to enhance students' motivation and manage cognitive load. To achieve the research objectives, in this study a mixed-method research design has been adopted in this study and four research instruments have been utilized such as 1) IMMS, 2) NASA-TLX, 3) Evaluation Module Score and 4) Interview protocol. In order to measure learners' motivation outcome, IMMS survey was conducted. NASATLX instrument is applied to know students cognitive load on using the tool. Interview protocol is conducted in order to explore students learning experience. To collect the data for the present study, participants are chosen as a simple random basis from a technical based university- a total of 128 (25 students for the control group and 103 students for the experimental group). Quantitative data analysis is performed using SPSS 18.0 version. In statistical analysis of quantitative data, preliminary analysis, inferential and Pearson correlational analysis are performed. Thematic analysis of qualitative data is accomplished to explore students learning experience. Findings from the IMMS (M = 4.04, SD = .13), NASA-TLX (M = 35.79, SD = 5.23) and MBTT Evaluation Module Score (M= 7. 83, SD = .98) indicated the important role of motivation and cognitive aspects instructional design on students' motivational outcome improvement, managed cognitive load and positive learning experience. Therefore, the present study supports the effectiveness of multimedia-based instructional design as an appropriate model for enhancing motivation and managing the cognitive load of the students for language learning. Furthermore, the present study of designing multimedia-based tense tool can contribute as an influential guide for future research on instructional design. A multimedia-based instructional design maintaining theoretical framework of motivation and cognitive load can come up with not only pedagogical implication but also ID design implications. It can contribute for instructional designers who are devoted to work for the language learners. Therefore, the need of designing a theoretically considered instructional material is crucial in every aspect of improving knowledge of English Tense learning.